The Determinants of Purchase Decisions for Subsidized Home Ownership Loans in Central Java - Syeranita Afani; Prihatiningsih Prihatiningsih; Mirasanti Wahyuni (CV Pena Jaya Pers, 2026)
Purpose: This study analyses the partial and simultaneous influence of promotion, service quality, and brand image on the purchase decision of subsidized home ownership loans (Kredit Pemilikan Rumah/KPR) among the community of Central Java, Indonesia. Design/methodology/approach: A quantitative explanatory design was employed. Primary data were collected online from 101 respondents residing in Central Java who had applied for, or already held, a subsidized KPR, selected through non-probability purposive sampling. Data were analysed using multiple linear regression with IBM SPSS Statistics 26, preceded by validity, reliability, and classical assumption tests. Findings: Promotion (t = 3.859; Sig. = 0.000), service quality (t = 4.078; Sig. = 0.000), and brand image (t = 2.068; Sig. = 0.041) each have a significant positive effect on purchase decisions, with service quality being the most dominant predictor. Simultaneously, the three variables significantly influence purchase decisions (F = 83.048; Sig. = 0.000), explaining 71.1% of the variance (Adjusted R² = 0.711). Research limitations/implications: The sample of 101 respondents, drawn through non-probability purposive sampling from cross-sectional data, limits the generalisability of the findings to the wider population of Central Java. Practical implications: The findings offer guidance for subsidized-mortgage distributor banks and housing-finance institutions in Central Java on strengthening promotional strategy, service quality, and brand image to broaden the reach of subsidized housing programmes. Originality/value: This study provides new empirical evidence on the determinants of subsidized KPR purchase decisions specifically in Central Java, a province with a high yet unevenly distributed realisation of subsidized housing loans, thereby addressing a research gap left by inconsistent prior findings. Paper type: Research paper.